The raw food detox diet : the five-step plan for vibrant health and maximum weight loss - Rose, Natalia (Harper Collins, 2006)
Discusses the health benefits of a raw foods diet, offers advice on how to make the transition to eating raw foods and flush out toxins that have built up in the body, and includes stage-specific recipes.